Cânula nasal de alto fluxo em pediatria: quando, como e por quê? - Samara Damin; Camila de Souza Espindola; Adriana Koliski; Marcelo Rodrigues; Valéria Cabral Neves; Debora Carla Chong Silva; José Eduardo Carreiro (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVES: to carry out a non-systematized bibliographic review and propose a flowchart for the use of HFNC in pediatrics. METHODOLOGY: this is a non-systematic review, where studies published in the last five years were selected with the aim of proposing a flowchart to guide the use of HFNC in pediatrics. RESULTS: we found 34 papers, fifteen were excluded because they only addressed the neonatal population, five because they did not address the topic, one because it did not have the full text and one because it was a study protocol. In addition to the twelve papers in the initial search, we included eleven more papers considered relevant to the objective of this review, selected from the reference lists. From the data obtained in the selected papers, we report on the definition of therapy, components of the device, parameters to be adjusted, mechanisms of action, indications and contraindications, benefits and possible complications of its use, resulting in a flowchart for using this treatment modality. CONCLUSION: studies suggest that high flow is a safe, well-tolerated and easy-to-apply method. In addition, it can avoid the need for non-invasive and invasive mechanical ventilation. A flowchart to optimize its use in pediatrics can be advantageous for the success of therapy.